INSTUMENT PEMBELAJARAN PSIKOMOTORIK - Umam, M. Khotibul; Rohati, Siti; Nugraha, Enung; Kultsum, Umi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses psychomotor learning tools in education. Psychomotor refers to the skills or capacity to act after students have undergone educational experiences. The purpose of measuring the psychomotor domain is not only to enhance students' performance in achieving educational goals in the psychomotor field but also to improve various aspects of students' movements and skills. This study uses a literature research method to deepen understanding of psychomotor learning tools. These results explain the meaning of psychomotor in learning, the nature of psychomotor education, the stages of psychomotor development, the objectives of psychomotor education, and other instruments in psychomotor assessment such as rating scales, observation sheets, assessment rubrics and performance tests. Psychomotor education instruments play an important role in measuring and evaluating students' physical abilities, enabling teachers to provide constructive feedback and design more effective education.